2021
DOI: 10.1038/s41598-021-87612-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of physical activity before and during pregnancy on infant’s sleep and neurodevelopment at 1-year-old

Abstract: The aim of this study was to investigate the association between maternal physical activity (PA) before and during pregnancy and sleep and developmental problems in 1-year-old infants. We used data from a nationwide cohort study in Japan that registered 103,062 pregnancies between 2011 and 2014. Participants were asked about their PA before and during pregnancy, and the sleep and development of their children at the age of 1 year. Maternal PA was estimated using the International Physical Activity Questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 45 publications
(22 reference statements)
0
17
0
Order By: Relevance
“…Alternatively, evidence showed that women with GDM have higher depressive symptoms (e.g., anhedonia; Wilson et al, 2020 ), which have been associated with lower motivation to conduct physical activity ( Carter and Swardfager, 2016 ). In previous studies, lower maternal physical activity during the perinatal period was associated with higher sleep problems in infants ( Nakahara et al, 2021 ).…”
Section: Discussionmentioning
confidence: 79%
“…Alternatively, evidence showed that women with GDM have higher depressive symptoms (e.g., anhedonia; Wilson et al, 2020 ), which have been associated with lower motivation to conduct physical activity ( Carter and Swardfager, 2016 ). In previous studies, lower maternal physical activity during the perinatal period was associated with higher sleep problems in infants ( Nakahara et al, 2021 ).…”
Section: Discussionmentioning
confidence: 79%
“…The publication year of included studies ranged from 1996 39,52 to 2021 50 . Four studies (29%) were from the United States of America 39-41,47 , two (14%) were from Norway 43,45 , while there was one (7%) study each from Brazil 42 , Canada 48 , Denmark 46 , Japan 50 , New Zealand 52 , Poland 51 , and Spain 44 . One study 49 reported data on two samples – one from Finland and one from the Netherlands.…”
Section: Resultsmentioning
confidence: 99%
“…Four (29%) experimental studies were included (three RCTs 43,45,48 and one long-term follow-up of two RCTs 49 ), and with sample sizes ranging from n=18 48 to n=336 45 . Ten (71%) observational studies were included (six prospective 39-42,47,51 and four retrospective 44,46,50,52 ) with the sample sizes ranging from 40 39 to 74,971 50 .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, recall bias regarding the assessment of PA levels before pregnancy using the IPAQ short form during the first trimester of pregnancy is a limitation. However, some previous studies have followed this procedure [ 4 , 19 , 41 ]. Moreover, the use of the IPAQ short form is one of the best ways to assess a birth cohort study from the perspective of feasibility.…”
Section: Discussionmentioning
confidence: 99%